Ambient air pollution, blood mitochondrial DNA copy number and telomere length in a panel of diabetes patients. (24th August 2015) - Xia, Yongjie; Chen, Renjie; Wang, Cuicui; Cai, Jing; Wang, Lianghui; Zhao, Zhuohui; Qian, Ji; Kan, Haidong
Abstract: Context : Several previous studies proposed a link between particulate matter (PM) pollution and mitochondrial DNA copy number (MtDNAcn) and telomere length (TL). However, this evidence is quite limited and inconsistent, especially on how the particle size affects the associations and on whether there exists such an association with gaseous pollutants. Objective : We aimed to investigate the short-term associations of size-fractionated PM and gaseous pollutants with blood MtDNAcn and TL. Methods : We conducted a longitudinal panel study involving 6 repeated measurements among 35 Type 2 diabetes patients in Shanghai, China from April to June 2013. We measured the real-time concentrations of size-fractionated PM (0.25–10 μm) and criteria gaseous pollutants. Blood MtDNAcn and TL were tested by a quantitative real-time PCR–based assay. Linear mixed-effect models were used to explore their short-term associations using multiple lag periods, after controlling for individual characteristics, time trends and weather conditions. Results : In general, there were inverse but statistically non-significant associations between all pollutants and MtDNAcn. Coarse PM appeared to be more closely linked with MtDNAcn than smaller PM. The associations between various air pollutants and TL were generally positive but very weak. There were no clear lag patterns for these associations. The associations between air pollutants and MtDNAcn and TL were strengthened but still not significant among those who did not take statins regularly. Conclusions : This study did not support short-term associations of PM or gaseous pollutants with blood MtDNAcn and TL in type 2 diabetes patients.